Digital Marketing Communications: Selection Criteria - Kapustina, Larisa; Gaiterova, Olga; Izakova, Natalya; Lazukov, Maksim (KnE Social Sciences, 2021)
This article discusses the concepts of digital and internet marketing and analyzes the classification of digital marketing communications. The purpose of the study is to develop criteria, a methodological approach to selecting the most appropriate digital marketing tools for a particular enterprise and market, and a system of indicators for evaluating the effectiveness of the marketing communications complex. The methodological approach is applied to small businesses in the retail market of cut flowers. For a specific company digital advertising, launching an internet site, maintaining social networks and search marketing were selected. Calculations of marketing communications performance indicators have shown that the use of digital marketing tools leads to a positive financial result. The survey has established that digital marketing is broader than internet marketing and includes the following media channels: social media marketing, digital television, content marketing, e-mail marketing, web site, SEO, Banner Ads, mobile marketing, streaming platforms, digital billboards. For specific purposes and markets it is sufficient to use not all, but part of the digital communication tools. The criteria for their selection are proposed: the marketing budget, the goals of the marketing strategy, the age of the audience, the competence of the company’s staff and the frequency of use of digital marketing tools. To assess the effectiveness of digital marketing communications a system of indicators is proposed that includes such indicators as: ROMI (Return on Marketing Investment), site traffic; profitability of sales on the Internet, increase in net profit, NPV (Net Present Value), popularity of certain pages of the site; information about the sources of transition to the site; duration of stay on the site; triggers for performing targeted actions; conversion and Web Analytics indexes. Keywords: digital marketing, digital marketing communications, digital media channels